Oral Rehabilitation and Management for Secondary Sjögren’s Syndrome in a Child - Tatiana Kelly da Silva Fidalgo; Carla Nogueira; Marcia Rejane Thomas Canabarro Andrade; Andrea Graciene Lopez Ramos Valente; Patricia Nivoloni Tannure (Case Reports in Dentistry)
The aim of this paper is to describe a rare case report of a pediatric patient with secondary Sjögren’s syndrome (SSS). A 12-year-old female child was referred to the Pediatric Dentistry Clinic with the chief complaint of tooth pain, dry mouth, and tooth sensibility. The patient was submitted to orthodontic treatment prior to syndrome diagnosis. The clinical treatment consisted of the interruption of orthodontic treatment and restoring the oral condition with dental treatment and the use of artificial saliva in an innovative apparatus. Dental therapy involved the control of dental caries, periodontal disease, and opportunistic fungal infections and the use of fluoride-rich solutions. The present clinical case describes clinical and laboratory aspects of SSS in pediatric patients. The management of the oral findings promoted an improvement in the oral health status and quality of life of the child.